Effects of solid lubricants on wire and arc additive manufactured structures. (April 2014) - Adebayo, Adeyinka; Mehnen, Jörn; Tonnellier, Xavier
This article reports a systematic study which examines the use of solid lubricants in the sequential deposition and machining of wire and arc additive manufactured parts and characterises the effects of solid lubricants on the microstructure. This article also describes the microstructure developed and the effect on microhardness by manual cleaning of deposited layers with acetone. Mild steel wire consumable electrode G3Si1 with the diameter of 0.8 mm was used. The use of graphite and molybdenum disulphide as solid lubricants in machining was also studied and a scanning electron microscope was used in detecting any form of lubricant contamination. A systematic study shows that a significant amount of solid lubricant contamination can be found in the deposited material. Furthermore, the results indicate that even cleaning of the wire and arc additive manufactured surfaces with acetone prior to the weld deposition can affect the microstructure of the deposited material.